Hepatitis E Virus Persistence and/or Replication in the Peripheral Blood Mononuclear Cells of Acute HEV-Infected Patients - Sayed, Ibrahim M.; Abd Elhameed, Zeinab A.; Abd El-Kareem, Doaa M.; Abdel-Malek, Mohamed A. Y.; Ali, Mohamed E.; Ibrahim, Maggie A.; Sayed, Ayat Abdel-Rahman; Khalaf, Khaled Abo bakr; Abdel-Wahid, Lobna; El-Mokhtar, Mohamed A. (Frontiers in Microbiology, 2021)
Background: Hepatitis E virus (HEV) infection causes about 14 million infections with 300000 deaths and 5200 stillbirths worldwide annually. Extrahepatic manifestations are reported with HEV infections such as renal, neurological, and hematological disorders. Recently, we reported that stool-derived HEV-1 replicates efficiently in human monocytes and macrophages in vitro. However, another study reported the presence of viral RNA but no evidence of replication in the PBMCs of acute hepatitis E (AHE) patients. Therefore, the replication of HEV in PBMCs during AHE infection is not completely understood. Methods: PBMCs were isolated from AHE patients (n=17) enrolled in Assiut University Hospitals, Egypt. The viral load, positive (+) and negative (-) HEV RNA strands and viral protein were assessed. The gene expression profile of PBMCs from AHE patients was assessed. In addition, the level of cytokines was measured in the plasma of the patients. Results: HEV RNA was detected in the PBMCs of AHE patients. The median of HEV load in the PBMCs was 1.34x103 IU/ml. A negative HEV RNA strand and HEV ORF2 protein were recorded in 4/17 (23.5%) of the PBMCs. Upregulation of inflammatory transcripts and increased plasma cytokines were recorded in the AHE patients compared to healthy individuals, with significantly elevated transcripts and plasma cytokines in the PBMCs with detectable (+) and (-) RNA strands compared to the PBMCs with detectable (+) RNA strand only. There was no significant difference in terms of age, sex, and liver function tests between AHE patients with detectable (+) and (-) RNA strands in the PBMCs and AHE patients (+) RNA strand only. Conclusion: Our study showed evidence for in vivo HEV persistence and replication in the PBMCs of AHE patients. The replication of HEV in the PBMCs was associated with an enhanced immune response which could affect the pathogenesis of HEV.